'Swallow it': Imagining Incest in Inter-war Writing on the Brontës. (2nd January 2019) - Pouliot, Amber
Abstract : For nearly one hundred years, sex, drugs and violence have featured in biographical fiction and drama about the Brontës. This paper focuses on the pervasiveness of fantasies of incest within the family. Influenced by the ambiguous sibling/lover relationship between Cathy and Heathcliff in Wuthering Heights (1847), biographers and creative writers from the nineteenth century to the present have characterized the relationship between Branwell and his sisters as subversively sexual. This paper traces the long history of how incest became embedded in the Brontë narrative – from Gaskell's 1857 biography, The Life of Charlotte Brontë, to Polly Teale's twenty-first-century drama, Brontë – but it focuses on the inter-war period, when biographical fiction and drama about the family first developed. It argues that unless we pay attention to the history of their representation, we will continue to see the same version of the Brontë story again and again.